Educating with Love: Inclusive Christian Religious Education Strategies to Answer the Challenges of Diversity in the Modern Era - Bole, Afriani Sriyanti; Rangga, Oktaviaunus (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2025)
This research aims to formulate an inclusive Christian Religious Education (CRE) strategy by making love the core pedagogical principle in responding to the challenges of diversity in the modern era. The problem addressed is the prevalent tendency toward exclusive and normative CRE approaches, which are often less relevant in diverse societies. The methodology employed is qualitative descriptive through a literature review of theological and pedagogical works. The novelty of this study lies in integrating love as an educational approach that is not only a taught value but also a teaching method and a transformative goal. The findings indicate that love can foster dialogical and empathetic relationships in the learning process, strengthen Christian identity without being exclusive, and empower teachers to act as facilitators of reconciliation. Thus, this approach enables CRE to be relevant and contextual, shaping students with Christian character who are ready to be agents of peace in a pluralistic society.